A STATUS REVIEW OF THE HYDROLOGICAL CHARACTERIZATION OF THE BASEMENT COMPLEX AQUIFERS IN TARABA STATE, N. E. NIGERIA - OKEKE, O.C; OMOKO, E.N. (IJRDO-Journal of Applied Science, 2017)
The availability and access to fresh water is an important issue all over the world. Groundwaterconstitutes the only reliable water supply for drinking and irrigation purposes. Recently there hasbeen increased interest in ground water resources resulting from a combination of an increase inits development for public and domestic use; an increase in mining, agricultural, and industrialactivities which might impact ground water quality; and an increase in studies of alreadycontaminated aquifers. Decision-making agencies involved in these groundwater activitiesrequire studies of the aquifers to develop reliable information on the hydrologic properties andbehaviour of aquifers and aquitards. Aquifer testing is a common tool used by hydrogeologists tocharacterize aquifers flow system boundaries. The most reliable type of aquifer test usuallyconducted is a pumping test. Pumping tests are a practical and reliable means of estimating aquiferhydraulic properties, well performance, yield, zone of influence of the well and boundaryconditions. Proper pumping test practices greatly assist in the interpretation and the value of thepumping test data. This paper is a review of methods of pumping test analysis and use of hydraulicparameters obtained in characterization of aquifer. A case history of the use of pumping testanalysis in aquifer characterization in some parts of Nigeria is also highlighted.